2016
DOI: 10.4049/jimmunol.1600658
|View full text |Cite
|
Sign up to set email alerts
|

MK2/3 Are Pivotal for IL-33–Induced and Mast Cell–Dependent Leukocyte Recruitment and the Resulting Skin Inflammation

Abstract: The IL-1R family member IL-33R mediates Fcε-receptor-I (FcεRI)-independent activation of mast cells leading to NF-κB activation and consequently the production of cytokines. IL-33 also induces the activation of MAPKs, such as p38. We aimed to define the relevance of the p38-targets, the MAPK-activated protein kinases 2 and 3 (MK2 and MK3) in IL-33-induced signaling and the resulting mast cell effector functions in vitro and in vivo. We demonstrate that the IL-33-induced IL-6 and IL-13 production strongly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 50 publications
8
86
1
Order By: Relevance
“…Confirming the in vivo findings, we found that MC stimulation with ATP in vitro resulted in prominent degranulation and histamine release but not in TNF production (Fig 2, I-K), whereas in contrast, IL-33 has been demonstrated to induce TNF production in vitro and MC degranulation in vivo but not in vitro. 7 Our data indicate that IL-33 signaling by MCs and amplification of stress responses by MC degranulation may be worth studying in more detail in the context of human inflammatory skin diseases. The observed mechanisms should have an impact on therapeutic decisions in cases of contact sensitivity which may be difficult to manage.…”
Section: Mast Cells Initiate the Vascular Response To Contact Allergementioning
confidence: 78%
“…Confirming the in vivo findings, we found that MC stimulation with ATP in vitro resulted in prominent degranulation and histamine release but not in TNF production (Fig 2, I-K), whereas in contrast, IL-33 has been demonstrated to induce TNF production in vitro and MC degranulation in vivo but not in vitro. 7 Our data indicate that IL-33 signaling by MCs and amplification of stress responses by MC degranulation may be worth studying in more detail in the context of human inflammatory skin diseases. The observed mechanisms should have an impact on therapeutic decisions in cases of contact sensitivity which may be difficult to manage.…”
Section: Mast Cells Initiate the Vascular Response To Contact Allergementioning
confidence: 78%
“…IL‐33 can serve as a potent activator of MCs and has been reported to promote survival, maturation, migration, adhesion, and the production of several pro‐inflammatory cytokines (eg, IL‐4, IL‐5, IL‐6, IL‐8, and IL‐13) and chemokines (eg, MIP‐1α and MCP‐1) in these cells . In addition, in the presence of SCF, IL‐33 can also induce TNF production in MCs via a MK2/3‐, ERK1/2‐, and PI3K‐dependent pathway . Recently, Taracanova et al have shown that IL‐33 and SP together amplify TNF secretion from MCs, which is mediated by the interaction of NK‐1R and ST2 receptors .…”
Section: Alarmin Receptorsmentioning
confidence: 99%
“…[250][251][252][253][254][255][256][257][258][259][260] In addition, in the presence of SCF, IL-33 can also induce TNF production in MCs via a MK2/3-, ERK1/2-, and PI3K-dependent pathway. 261 Recently, Taracanova et al have shown that IL-33 and SP together amplify TNF secretion from MCs, which is mediated by the interaction of NK-1R and ST2 receptors. 262 In addition, IL-33 and…”
Section: St2/il-33mentioning
confidence: 99%
“…The effector functions of the IL‐33R depend on the IL‐1 associated protein (IL‐1Racp) and can be modulated by c‐Kit activation in mast cells . Furthermore, IL‐33 via IL‐33R induces the MyD88‐TAK1‐IKK2‐dependent activation of NF‐κB and the activation of the p38‐MK2/3 signaling axis in mast cells . Thereby, MK2/3 mediates the IL‐33‐induced signaling via the PI3K‐PKB/Akt‐mTOR‐ribosomal S6 kinases (RSKs) pathway and stabilizes the mRNAs of IL‐6 and TNFα .…”
Section: Introductionmentioning
confidence: 99%